THE RELATIONSHIP BETWEEN PARENT PARENTING PATTERNS AND LEARNING ACHIEVEMENT IN V-GRADE SCHOOL CHILDREN AT SDN KERONCONG MAS PERMAI - Devia Nurdiyanti; Alfika Safitri; Rina Puspita Sari (Journal of Vocational Nursing, 2023)
Introduction: Parenting is a comprehensive interaction between parents and children. School age in Indonesia is between 7 and 12 years old. This study aims to determine the relationship between parenting parents and learning achievement in fifth grade school children at SD Keroncong Mas Permai. Methods: This research is quantitative with a cross sectional study design with a sample of 104 students, The sampling used was Proportional Stratified Random Sampling. Data collection used a questionnaire on parenting patterns and the results of fifth grade students' even semester report cards. The analysis used is bivariate Pearson correlation with a significance level of a<0.05. Results: This research shows that some parents apply authoritarian parenting with a percentage of 49.0% and permissive have no percentage, while most parents apply democratic parenting with a percentage of 51.0%, so parents have an adequate role. major in educating children with the achievement of student achievement in school. The results of the Pearson correlation test with a significance level of a < 0.05 obtained a = 0.000, where a < 0.05 means there is a significant relationship between parenting patterns and learning achievement in class V school children at SDN Keroncong Mas Permai. Conclusions: Based on the results of the analysis above, it was found that there was a relationship between parenting parents and learning achievement in fifth grade school children at SDN Keroncong Mas Permai.